Exertional heat illness risk factors and physiological responses of youth football players - Susan W. Yeargin; John J. Dickinson; Dawn M. Emerson; Jessica Koller; Toni M. Torres-McGehee; Zachary Y. Kerr (Elsevier, 2021)
Objective: To determine which intrinsic and extrinsic exertional heat illness (EHI) risk factors exist in youth American football players and observe perceptual and physiological responses of players during events (games and practices). Methods: Cross-sectional cohort study observing 63 youth football players, varying in position. Independent variables were league (weight-restricted (WR, n = 27) and age-restricted (AR, n = 36)) and event type. Dependent variables were anthropometrics, work-to-rest ratio, and wet bulb globe temperature. Descriptive variables included preparticipation examination and uniform configuration. A subset of 16 players participated in physiological variables (heart rate and gastrointestinal temperature). Data collection occurred on 7 AR and 8 WR nonconsecutive practices and the first 3 games of the season. Results: Mean values for anthropometric variables were higher (p < 0.05) in the AR league than the WR league. Work time (χ2 (1,111) = 4.232; p = 0.039) and rest time (χ2 (1,111) = 43.41; p < 0.001) were significantly greater for games, but ratios were significantly higher for practices (χ2 (1,111) = 40.62; p < 0.001). The majority of events (77%) observed were in black and red flag wet bulb globe temperature risk categories. A total of 57% of the players had a preparticipation examination, and up to 82% of events observed were in full uniforms. Individual gastrointestinal temperature and heart rate responses ranged widely and no players reached critical thresholds. Conclusion: Extrinsic (disproportionate work ratios, environmental conditions) and intrinsic (higher body mass index) EHI risk factors exist in youth football. Certain risk factors may be influenced by event and league type. National youth football organizations need to create thorough guidelines that address EHI risk factors for local leagues to adopt.